Reliability maintenance and logistic support a life cycle approach - Dinesh Kumar, U.; Crocker, John; Knezevic, Jezdimir, 1953-; El-Haram, Mohamed (Kluwer Academic, 2000)
Reliability, Maintainability, and Supportability play a crucial role in achieving a competitive product. The main objective of this book is to provide an integrated approach to reliability, maintainability, maintenance and logistic support analysis.